OPTIMALISASI BUDAYA KERJA PERUSAHAAN UNTUK MENINGKATKAN KEPUASAN KERJA KARYAWAN - Dwiki Ananto Yudo (Unitri Press, 2021)
This study aims to determined how organizational culture can increase employee job satisfaction. In compiling this paper, the literature study method was used by conducting a literature review obtained from journals, books, and research. The results of the paper concluded that organizational culture in a company can affect the level of job satisfaction of an employee. The reason was because organizational culture can shape employee behavior in accordance with the company's wishes, so that the presence of an employee in the company can be felt by the company's leadership. Organizational culture in a company must be built on the basis of fulfilling the interests of the company and employees, so that employees have job satisfaction, and can provided their potential to the maximum in accordance with the wishes of the company